Vol. 3, No. 1, September 2021 - Said Anna Fauza; Ani Yunaningsih (Scientia Regendi, 2021)
This study aims to explain the effect of figurative competence on the effectiveness of character building of students. The research was conducted at the Pusdik Intelkam Polri Soreang Bandung by taking a sample of 75 respondents. The research method used is quantitative methods. The data collection techniques used research instruments such as questionnaires, interviews and observations. The analysis used is descriptive analysis, path analysis and data verification. The results of the study are: there is an influence of patent competence on work effectiveness.